Unlock the Potentials of Large-Element-Spacing Arrays: A Meta-Lens Solution for Grating-Lobe Suppression and Gain Enhancement - Zhengmei Wang; Shan Lin; Yuehe Ge; Zhizhang (David) Chen; Jingjing Zhao; Jiahong Chen; Ziheng Zhou; Trevor S. Bird (Electromagnetic Science)
Large-element-spacing (LES) antenna arrays present an attractive proposition with their cost-effectiveness and simplified structures. However, they often encounter the challenge of high-level grating lobes. This paper proposes a novel meta-lens methodology to effectively address the grating lobe issue in fixed-beam LES arrays. The proposed approach involves strategically positioning a meta-lens above the LES arrays at a suitable vertical distance. This setup enables precise manipulation and compensation of the near-field phase, resulting in the suppression or elimination of grating lobes without introducing additional design complexity. Comprehensive theoretical analyses, meticulous design calculations employing efficient numerical methods, rigorous field simulations, and practical experiments are conducted. The results demonstrate that our meta-lens solution achieves significant grating-lobe suppressions and substantial gain enhancements with only a marginal increase in system profile or volume. The proposed meta-lens approach is versatile and applicable to various LES antenna arrays, including sparse/thinned arrays, regardless of their size, element spacing, and configuration (uniform or non-uniform, periodic or aperiodic).